(untitled) (Experimental biology, 2022)
In the present study, we searched for the composition of cheap nutrient media. We grew local isolates of Beauveria bassiana (Ascomycota: Clavicipitaceae) isolated from various natural sources in Kyrgyzstan. To produce biomass from strains of Beauveria bassiana in laboratory conditions and determine its entomopathogenic activity, food industry wastes were used: pea groats, oatmeal and soy flour. Strains 501Bb, 502Bb and 503Bb gave a tremendous growth of mycelium and conidia formation on the surface of oatmeal and pea groats when counting the resulting conidia in 1g of the biomass, the density of conidia was 1.2-1.4 x 109 spores/ml within 15 days. Weak growth was noted on soy flour; conidia was 1.0x104 spores/ml.